Teaching Merton to Undergraduates - Rausch, Thomas P. (Horizons, 1995)
Thomas Merton is one of the most significant figures in twentieth-century Catholicism. His books are still to be found in almost any bookstore with a section devoted to religion. Yet today, just over twenty-five years after his death, both Merton himself and the monastic life he represented are virtually unknown to most Roman Catholic undergraduates. This article describes a seminar on Merton offered for undergraduates. It outlines the books and articles used, the way the seminar was structured, and the reactions of the students, to Merton himself and to the issues he raises in his works.